Cortical Vein Thrombosis in a Case of Clinically Isolated Syndrome and Psoriasis—A Case Report and Review of Literature. Issue 1 (June 2021) - Agadi, Jagadish B.; Viswanathan, Lakshminarayanapuram Gopal; Kumar, Sujit; Pramod, Manithody Narayan-Bhat
Cortical vein/venous sinus thrombosis (CVT) occurring in the context of a clinically isolated syndrome (CIS) is highly unusual. Our patient presented with dorsal cord demyelination and psoriasis. She developed severe headache post-lumbar puncture, which was followed by focal seizures. She had developed CVT with a hemorrhagic infarct in the left parietal region. Multiple factors, both patient related and as a consequence of treatment and management, may have contributed to this outcome. We aim to discuss the relevance of this rare finding with a brief review of literature.